Aflatoxin Contamination of Cottonseed From Pink Bollworm Damaged Bolls - Cotty, P. J. (College of Agriculture, University of Arizona (Tucson, AZ), 1989)
Aflatoxin contamination of cottonseed from bolls damaged by the pink bollworm was compared with contamination of cottonseed from undamaged bolls. Cottonseed produced in pink bollworm damaged bolls was the predominant source of aflatoxin contaminated cottonseed.